Application of a fully 3D printed carbon electrode for the double potential step Chronoamperometric determination of 2,4-dinitrophenol in environmental water samples - Shaw, Daniel Steven; Rymansaib, Zuhayr; Iravani, Pejman; Honeychurch, Kevin C. (Frontiers in Chemistry, 2025)
IntroductionThe detection of nitrophenolic compounds in environmental water sources is critical due to their toxicity and persistence. This study presents the first reported application of a fully 3D printed carbon nanofiber-graphite-polystyrene working electrode for the electrochemical determination of 2,4-dinitrophenol (2,4-DNP), offering a novel and potentially cost-effective alternative to traditionally fabricated electrodes.MethodsInitial characterisation of 2,4-DNP was performed using cyclic voltammetry across a pH range of 2-8 to investigate its redox behaviour. A double potential step chronoamperometric technique was then employed, with step potentials set at −1.4 V and +0.8 V. Calibration was conducted using standard solutions of 2,4-DNP, and the method was validated using both fortified and unfortified environmental pond water samples.ResultsCyclic voltammetry revealed two reduction peaks during the initial negative scan, attributed to the reduction of the nitro groups to hydroxylamines, followed by two oxidation peaks on the positive scan corresponding to the re-oxidation of these hydroxylamines. All peaks exhibited pH dependence. The chronoamperometric calibration curve was linear over the concentration range of 50 μM to 1.0 mM (R2 = 0.9978), with a detection limit of 7.8 μM (S/N = 3). Analysis of pond water samples yielded a mean recovery of 106% with a coefficient of variation of 3.6% at 50 μM.DiscussionThe results demonstrate that 3D printed carbon nanofiber-graphite-polystyrene electrodes are effective for the determination of 2,4-DNP in environmental water samples. The method provides reliable quantification with good sensitivity and reproducibility, highlighting the potential of additive manufacturing in the development of electrochemical sensors for environmental monitoring.